Analisis Penerapan Pendidikan Karakter dalam Pembelajaran Matematika di SMP Negeri 1 Simpangkatis Kelas VIII dan MA Muhammadiyah Gantung Kelas X MIA - Intan Juwita; Pendi P; Eka Rachma Kurniasi (Pendidikan Matematika STKIP Kusuma Negara, 2020)
This study aims to discuss the analysis of the application of character education in mathematics learning at SMP Negeri 1 Simpangkatis class VIII and MA Muhammadiyah Gantung class X MIA. Mathematics learning is used as a medium and a vehicle for character building. By advancing character education in mathematics, Mathematics Learning is no longer to support the development of the cognitive domain but also to develop the affective domain. The research method used a qualitative approach with qualitative descriptive methods. Data collection used observation and interview sheets. The research findings show that character education has been applied in mathematics learning at SMP Negeri 1 Simpangkatis and MA Muhammadiyah Gantung. As for learning activities that can foster character values, including praying together, the teacher giving worksheets and students working in groups, students presenting the results of their work in front of the class. The character referred to is having a strong attitude, discipline, tolerance, solidarity, hard work, responsibility, competitiveness and sportsmanship.